A Comprehensive Study on Smart Brain Chip Technologies for Precision Mental Health Monitoring and Treatment - Yeshpatel, Viroja; Solanki, Ashutosh; Mehta, Nihar; Dilavarsinh, Atodariya Rushikumar; Ashokbhai, Vasoya Divyaben; Thakkar, Vishwa Alpeshbhai; Dave, Vivek (Journal of Neonatal Surgery, 2025)
Smart brain-chip technologies have improved both the accuracy and time for diagnostic and treatment of mental health. This article offers an in-depth look at neural interfaces that have been developed, used, and have had practical implications in the treatment of mental disorders via real-time cognitive function simulation. Thanks to multidisciplinary merging of neuroimaging, the most advanced machine learning as well as engineering, these devices will make room for the development of new therapies useful for e.g. depression, anxiety, bipolar disorder, and PTSD. The article points to the fact that intelligent brain chips are able to carry out very precise diagnostics and also allow fast treatment, which, in turn, can lead to positive outcomes in patients. Nevertheless, there are still some issues that need to be answered such as the infringement of data privacy, the risks of ethical nature, and the effects of neural interventions in the future that are not yet well-known. The study deals with these problems by connecting them to issues found in the application of smart brain chips in mental health care.